Upaya Kepala Sekolah dalam Mencegah Perilaku Bullying di Sekolah Menengah Kejuruan: The Headmaster Efforts to Prevent Bullying Behavior at Vocational School - Dewi Rubiyati; Zaenullah; Nurlaela; Risa Shoffia (STAI Ma'had Aly Al-Hikam Malang, 2025)
The purpose of this study was to analyze how was the efforts of the principal of SMKN 1 Sedan in preventing bullying. This study used a qualitative research method using a case study. Data collection techniques included detailed interviews and observations. Data analysis involved data reduction, data presentation, data validity checking through data triangulation, and drawing conclusions. The research findings revealed that the headmaster of SMKN 1 Sedan conducted a Bullying Prevention Socialization program, which included the presentation of material on bullying and evaluation of the activity using pre- and post-tests. Involving Islamic Religious Education Teachers to Implement Islamic Values ​​to Students. In addition to conducting outreach activities to prevent bullying, the Principal of SMKN 1 Sedan, through Islamic Religious Education teachers, also implements Islamic values ​​regarding moral values ​​to create quality students/learners with noble character.